Organizational Objectives And Winning: An Examination Of The Nfl. - Latham, Donald R.; Stewart, David W. (Academy of Management Journal, 1981)
The article presents information on a study which examined the managerial objectives of the National Football League (NFL). The authors discuss the generally accepted success criteria for NFL teams...